Hubungan Psychological Well-Being dengan Work-Life Balance pada Dosen Unisba - Yvon Alifa Rakhman; Suhana (UNISBA Press, 2023)
Abstract. Psychological well-being is a condition of individuals who are able to function optimally in self-acceptance, have autonomy, can control their environment, have goals to achieve in life and have meaning in life, have good interpersonal relationships, and have a sense of wanting to grow and develop (1). Work-life balance is an individual's ability to meet goals and demands in two domains, namely work and personal life (2). The purpose of this study is to determine the relationship between psychological well-being and work-life balance in Bandung Islamic University lecturers. The research method used is correlational quantitative. The subjects in this study were 84 lecturers at Bandung Islamic University. The measurement tool used is the work-life balance questionnaire belonging to Fisher et al. (3) which has been adapted by Gunawan et al. (4), and Carol D. Ryff's psychological well-being measuring tool which has been adapted by Engger (5). The results of this study indicate that the significance value is 0.000 <0.05, meaning that there is a significant relationship between psychological well-being and work-life balance in Bandung Islamic University lecturers with a correlation coefficient value of 0.506, means that the level of strength of the relationship (correlation) between the two variables is classified as moderate. The correlation coefficient number is positive, meaning that the relationship between the two variables is positive. Abstrak. Psychological well-being merupakan keadaan individu yang mampu berfungsi secara optimal dalam penerimaan diri, memiliki otonomi, dapat menguasai lingkungannya, memiliki tujuan untuk dicapai dalam hidup dan kebermaknaan dalam hidup, memiliki hubungan interpersonal yang baik, dan memiliki rasa ingin tumbuh dan berkembang (1). Work-life balance merupakan kemampuan individu dalam memenuhi tujuan dan tuntutan di dua domain, yaitu pekerjaan dan kehidupan pribadi (2). Tujuan dari penelitian ini yaitu untuk mengetahui hubungan antara psychological well-being dengan work-life balance pada dosen Universitas Islam Bandung. Metode penelitian yang digunakan yaitu kuantitatif korelasional. Subjek dalam penelitian ini yaitu sebanyak 84 dosen Universitas Islam Bandung. Alat ukur yang digunakan yaitu work-life balance questionnaire milik Fisher et al. (3) yang telah diadaptasi oleh Gunawan et al. (4), serta alat ukur psychological well-being milik Carol D. Ryff yang sudah diadaptasi oleh Engger (5). Hasil dari penelitian ini menunjukkan bahwa nilai signifikansi 0.000 < 0.05, artinya terdapat hubungan yang signifikan antara psychological well-being dengan work-life balance pada dosen Universitas Islam Bandung dengan nilai koefisien korelasi sebesar 0.506, artinya tingkat kekuatan hubungan (korelasi) antara kedua variabel tersebut tergolong sedang. Angka koefisien korelasi bernilai positif, artinya hubungan antara kedua variabel tersebut adalah positif.